Frequency of complications of transurethral pneumatic lithotripsy in pediatric bladder stone disease. - Farman Ullah; Tanzeel Gazder; Sanjeet Therani; Izhar Ali; Hamza Akhtar; Usman Qamar; Syed Rabiullah; Mazahir Zulfiqar (International Journal of Endorsing Health Science Research, 2023)
Background: Despite advancements, underdeveloped countries continue to face the burden of widespread illness causing pain, often attributed to factors like low nutrition and recurring infections, particularly vitamin A deficiency. Methodology: This descriptive study employed a non probability convenient sampling technique and was conducted at the Urology Department of Lady Reading Hospital, Peshawar. The investigation spanned six months from January 25, 2019, to June 25, 2019. The study encompas sed a cohort of 369 patients, each subjected to comprehensive urine tests and detailed history and physical examinations. Procedures were performed under general anesthesia, utilizing Pediatric URS and pneumatic intracorporeal lithotripsy with Swiss lithoc last for bladder stone treatment. A 48 hour post treatment observation period assessed common intraoperative and postoperative consequences of transurethral pneumatic lithotripsy, including hematuria, bladder perforation, acute urine retention, and fever. Results: Among the participants, 32% were female, and 68% were male. Notably, 5% experienced bladder perforation, 7% had hematuria, 4% exhibited acute urinary retention, and 7% presented with fever. Conclusion: This study highlights complications of transurethral pneumatic lithotripsy in pediatric bladder stone disease, including bladder perforation, hematuria, acute urinary retention, and fever, providing crucial insights for clinical decisions.